"Iron Sharpens Iron" as a Negative Image: Challenging the Common Interpretation of Proverbs 27:17 - Giese, Ronald L. (Journal of Biblical literature, 2016)
Proverbs 27:17, "Iron sharpens iron, and one man sharpens the face his neighbor," is almost universally seen as positive. Some view this maxim as an example of "tough love," others as a rewording of a verse earlier in this passage, "Faithful are the wounds of a friend" (27:6). There is little evidence, however, for these interpretations, which appear to reflect modern connotations of "sharpness." In fact, the biblical evidence for parts of a face that are "sharp" suggests a more negative reading, for sharp eyes or a sharp tongue show an intent to do violence or bring about destruction. The usage of the LXX's verb for "sharpen" (...) elsewhere confirms this interpretation. Proverbs 27:17 may therefore be stating that, just as an iron hammer violently pounds out soft iron in the smithing process, so too may a same-gender neighbor engage in a similarly violent act, in a manner that is little different from that of a contentious wife. This study of the Hebrew and Greek verbs for "sharpen" suggests that v. 17 continues the idea of "friendships" to be avoided (vv. 13-16). The previous passage, then, teaches the positive aspects of friendship (vv. 1-10, esp. vv. 5-10), followed by the negative aspects in vv. 11-17.